DOES TYPE 1 DIABETES AFFECT ACHILLES TENDON RESPONSE TO A 10KM RUN?. Issue 7 (11th March 2014) - Wong, A; Docking, S; Cook, J; Gaida, J
Abstract : Background: Hyperglycaemia accelerates collagen cross-linking in tendons, which may manifest as an increased thickness or as an altered response to load. Type 1 diabetes mellitus (T1DM) is a unique population exhibiting hyperglycaemia independent of obesity and low physical activity. Ultrasound tissue characterisation (UTC) quantifies the structural integrity of a tendon based on the alignment of collagen, represented as echo-types (I-IV). Objective: To measure achilles tendon response to a 10km run among individuals with T1DM and controls. Design: In this case-control study, UTC scans were taken at day 0, 2, 4 after a 10 km run. Analysis of UTC scans was performed in a blinded fashion. Setting: Social running club for people with T1DM. Participants: Individuals with T1DM (n=7) were diagnosed 13±12 years ago. Control participants (n=10) had no diagnosis or family history of T1DM. Participants all regularly ran ≥5 km in a recreational capacity with an average weekly distance of 18±3 km. VISA-A scores were 94±11 (T1DM) and 94±10 (control). Risk factor assessment: The independent variable was diagnosis of T1DM (yes/no). HbA1c and blood glucose were also measured. Main outcome measurements: Tendon response to a 10km run measured with UTC was defined as the key outcome variable before data collection. Results: Baseline structure was the same in control and T1DM groups for all UTC four echo-types (I-IV) and for anteroposterior thickness (P>.05). Furthermore, no significant differences were observed within each group in response to the run. Conclusions: A novel finding that Achilles tendon baseline structure and response to a 10 km run over 4-days is the same in controls and T1DM. This suggests that T1DM individuals who are regularly physically active do not undergo the same structural changes to their Achilles tendon as previously demonstrated in the general diabetic population.